IMPLEMENTASI SMART CONTRACT DALAM TRANSAKSI KEUANGAN MIKRO ISLAM: ANALISIS KRITIS ATAS PARADIGMA SHARIAH COMPLIANCE BY DESIGN - Rani Anjarwati; Lulud Wijayanti (Jurnal Ekonomi Syariah Darussalam, 2026)
This research aims to analyze the implementation of smart contracts in Islamic microfinance transactions thru the Shariah Compliance by Design paradigm, as well as to identify the opportunities and challenges of its application in the modern Shariah financial system. The research uses a qualitative method with a normative juridical approach and conceptual analysis. The research results show that blockchain-based smart contracts can enhance the efficiency, transparency, accountability, and security of transactions thru the automation of contracts and real-time data recording. In addition, the Shariah Compliance by Design paradigm serves as a preventive model that integrates Shariah principles from the system design stage, thereby minimizing the risk of Shariah violations. However, its implementation still faces challenges related to the validity of digital ijab kabul, the accommodation of elements of niyyah, ridha, and ijtihad, as well as the limitations of regulations governing the use of such technology. Therefore, synergy between regulators, scholars, Islamic finance practitioners, and technology experts is needed to realize an innovative, safe, and sustainable Islamic microfinance system. Keywords: Smart Contract, Design, and Shariah Compliance